Competing patient and professional agendas in service development. Issue 6 (11th November 2014) - Wainwright, David; Boichat, Charlotte; M. McCracken, Lance
Abstract : Purpose: – The purpose of this paper is to engage stakeholders in the development of a community based chronic pain-management service and identify their different agendas for service design and delivery. Design/methodology/approach: – Data were collected using the Nominal Group Technique (NGT), a ten-step process that generates qualitative and quantitative data. Seven NGT groups were conducted in the south-west region of the UK, three with General Practitioners and nurses, three with chronic pain patients, and one with Healthcare Commissioners. Findings: – The patient agenda for service development focused on process of care issues particularly the need for deep- empathy and emotional support from providers, while professionals prioritised cost-effectiveness. While there was some overlap between agendas they were largely discrete and often contradictory. Research limitations/implications: – The findings imply service planners will need to make trade-offs between cost-containment and patient satisfaction. The methodology did not allow trade-offs to be put to participants in a structured form. However, such techniques are available, for example, Conjoint Analysis. There may also be value in bringing together patients and professionals in joint focus groups, to see if the gap between their different agendas can be bridged through discussion. Originality/value: – The findings provide a novel insight into the competing agendas of patients and professionals regarding service development and design which will be of value to service planners and managers as they strive to reconcile these differences.